EL CUMPLIMIENTO DE LAS BUENAS PRÁCTICAS AMBIENTALES EN ENTIDADES DEL SECTOR PÚBLICO, ENCAMINADAS A REDUCIR LA CONTAMINACIÓN DEL MEDIO AMBIENTE - ARPI HIDALGO, JOHANNA ESPERANZA (2016)
The Constitution of the Republic of Ecuador recognized as a Fundamental Right the right to live in a healthy environment free from pollution however this guarantee is not met in our country, where a daily series that attempt situations committed against the Environment. In this research work a doctrinal, legal and environmental best practice in public sector entities for the purpose study was conducted, national and international legal regime that protects the environment, and environmental management carried out by public entities were investigated of our country. From the collected research data the need to reform the law of legal Environmental management which dispersed manner regulate and penalize environmental offenses (crimes and misdemeanors), and the need for the National Assembly established a formal suit and materially in one law the procedure for administrative prosecution of environmental damage. In establishing the existence of the problem, I decided to study, in this paper that besides having a good theoretical basis presents factual data directly demonstrate the criteria of legal professionals and similarly contains a proposal for a legal order which contribute best way to punish behavior that endangers the environment and safeguard this right has been constantly violated in our country. 5 From this perspective I announce the contents thereof, and put it under the objective of sound and constructive reader.